Decision making under uncertainty in climate change mitigation: introducing multiple actor motivations, agency and influence. (7th February 2019) - Roelich, Katy; Giesekam, Jannik
ABSTRACT: Climate change mitigation has two main characteristics that interact to make it an extremely demanding challenge of governance: the complexity of the socio-technical systems that must be transformed to avoid climate change and the presence of profound uncertainties. A number of tools and approaches exist, which aim to help manage these challenges and support long-term decision making. However, most tools and approaches assume that there is one decision maker with clearly defined objectives. The interaction between decision makers with differing perspectives and agency is an additional uncertainty that is rarely addressed, despite the wide recognition that action is required at multiple scales and by multiple actors. This article draws inspiration from dynamic adaptive policy pathways to build on current decision support methods, extending analysis to include the perspectives and agency of multiple actors through a case study of the UK construction sector. The findings demonstrate the importance of considering alignment between perspectives, agency and potential actions when developing plans; the need for mobilizing and advocacy actions to build momentum for radical change; and the crucial influence of interaction between actors. The decision support approach presented could improve decision making by reflecting the diversity and interaction of actors; identifying short-term actions that connect to long-term goals and keeping future options open. Key policy insights Multiple actors, with differing motivations, agency and influence, must engage with climate change mitigation, but may not do so, if proposed actions do not align with their motivations or if they do not have agency to undertake specific actions. Current roadmaps, which assume there is one decision maker with control over a whole system, might overstate how effective proposed actions could be. Decision making under deep uncertainty needs to account for the motivations and agency of diverse decision makers and the interaction between these decision makers. This could increase the implementation and effectiveness of mitigation activities.